ACTIVITY TEST OF LEMONGRASS LEAF EXTRACT (CYMBOPOGON CITRATUS) AGAINST STREPTOCOCCUS MUTANS BACTERIA AND ESCHERCHIA COLI (Journal of Health, Technology and Science (JHTS), 2023)
ABSTRACTThis study aims to determine the antibacterial activity of lemongrass leaf extract (Cymbopogon citratus) against Streptococcus mutans  and Escherchia coli bacteria. This research method uses a Complete Randomized Design (RAL) consisting of 7 treatments and 4 repeats. The treatments are: P1 (negative control), P2 (10% concentration), P3 (20% concentration), P4 (30% concentration), P5 (40% concentration), P6 (50% concentration) and P7 (Amoxicillin positive control). The results showed that the concentration of lemongrass leaf extract (Cymbopogon citratus) has activity to inhibit the growth of Streptococcus mutans and Escherchia coli bacteria.  The results of the statistical analysis  of the Kruskall Wallis test  showed a significant value of 0.008 or